Penerapan Metode Ceramah Pada Siswa Sd Muhammadiyah 5: Kelebihan Dan Tantangannya - M Samarkhan Saedely (Journal of Sustainable Education, 2026)
The lecture method is a learning method still frequently used in elementary schools (SD) because it is considered practical and effective in conveying material to students. Although various modern and innovative learning methods have developed, the lecture method remains the preferred method for teachers in the learning process. This article aims to analyze the application of the lecture method to elementary school students and identify the advantages and challenges in its use. This research uses a literature study method by examining various educational theories from experts, such as Wina Sanjaya, Nana Sudjana, and Jean Piaget's cognitive development theory. The results of the study indicate that the lecture method has several advantages, such as time efficiency, ease of classroom management, and systematic and directed material delivery. However, this method also faces various challenges, especially because elementary school students tend to be active and require concrete, interesting, and interactive learning. Therefore, the lecture method needs to be combined with other learning methods to make the learning process more effective and in line with students' developmental needs.